Research on the Size Effect of Unstable Fracture Toughness by the Modified Maximum Tangential Stress (MMTS) Criterion - Jian Li; Zhao-Wen Du; Zhong-Ping Guo; De-Chun Ai (Advances in Civil Engineering)
This paper investigates the unstable fracture toughness of specimens of different heights using the double-K model for three-point bending tests on notched concrete beams. It is shown that unstable fracture toughness exhibits a significant size effect. The modified maximum tangential stress (MMTS) criterion is used to explain the size effect of unstable fracture toughness. The MMTS criterion considers the higher order terms of the Williams series expansion of the stress field. The results show that the MMTS criterion can reasonably estimate unstable fracture toughness. It is recommended that the minimum height of the specimen be 200 mm when three-point bending tests on notched beams are used to determine unstable fracture toughness.